Bread By-Product and Maize Silage as Alternative Ingredient Feeds for Production of Tenebrio molitor Larvae in High-Concentrate Substrates - Guillermo Fondevila; Ana Remiro; Sara Remón; Manuel Fondevila (Animals)
Bread by-product and maize silage as substrates for Tenebrio molitor larvae were studied in four isonitrogenous diets: a control substrate (CTL) made of wheat grain, wheat bran, and soybean meal and three diets where wheat grain and wheat bran were partly substituted with bread by-product (BBP) or with this and either a low (MSL) or high (MSH) proportion of maize silage (170 or 310 g/kg, respectively). Larval weight was weekly monitored, and the chemical composition of larvae and residual substrates was analyzed at the end of the experiment. Larvae fed CTL and BBP grew more than those fed MSL and MSH (p < 0.001). Feed intake was greatest for BBP (p < 0.001), and consequently, feed-to-gain ratio (F:G) was better for larvae fed CTL than BBP, and better for BBP than MSL and MSH (p < 0.001). Besides, total production of crude protein and ether extract were greater for CTL and BBP than for MSH and MSL (p < 0.001). The inclusion of bread by-product in the substrate did not affect growth performance, whereas diets including maize silage impaired larval growth, substrate intake, and F:G. Both by-products can be advantageously used for feeding T. molitor larvae, but the impairments in growth performance should be considered to optimize production costs.